A Review of Rangarajan Committee Report on Poverty Estimation. Issue 1 (April 2016) - Raveendran, G.
This article presents a review of the methodology recommended by the Rangarajan Committee for poverty estimation. In line with the existing practice, the Committee has also recommended the use of absolute poverty measures. It, however, deviated from Tendulkar Committee method by anchoring the poverty lines on nutritional norms of calorie, protein and fat and deriving separate poverty lines for rural and urban areas. However, the use of average all India requirement of calorie, protein and fat for identifying food-deprived individual households resulted in false identification and under estimation of nutritionally deprived. The use of consumer expenditure data collected by using modified mixed reference period without verifying its quality, particularly the extent of telescopic errors due to the use of shorter reference period, design effect due to disproportionately larger representation of affluent households within a reduced sample size and non-sampling errors due to poor quality of field work made the entire exercise futile. Further, there does not exist any monthly per capita consumption expenditure fractile which met all the nutritional norms as claimed by the Committee and as such the selection of such a fractile as poverty line basket is doubtful. Above all, the poverty estimates given by the Committee for the years 2009–2010 and 2011–2012 lack credibility as the reductions in head count ratios over a 2-year period were unbelievably high in respect of states like Andhra Pradesh, Bihar, Rajasthan, etc. although the estimated reductions were not very much different from those given by the Tendulkar Committee.